Analisis Pengaruh Tata Kelola Perusahaan terhadap Struktur Modal dengan Kualitas Laporan Keuangan sebagai Mediator pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Johny Budiman; Helena Helena (Jurnal Manajemen Maranatha, 2017)
This study aims to determine the effect of corporate governance on the capital structure with the quality of the financial reports as a mediator. Independent variables used in this research is the size of the board, independent board composition, concentration of ownership and managerial ownership. As a control variable is profitability and quality of the financial reports as a mediating variable. Thecapital structure is measured by the debt ratio. Samples from this study were 217 companies listed on the Indonesia Stock Exchange in the period 2011-2015 and were selected using purposive sampling method. Data have been obtained will be tested with mulitiple linear regressios with SPSS version 21.0. The results of this study indicate that there is a significant influence between board composition, concentration of ownershipÂ  and managerial ownership on capital structure mediated by financial report quality. Â Keywords: Capital Structure; Corporate Governance; Debt Ratio; Quality of Financial Reporting